The Effect of Crossword Puzzles on Learners' Vocabulary Development in EFL Context - Ahmad Wefi; Dzulfikri Dzulfikri; Sonny Elfiyanto (STAI Miftahul Ula Nganjuk, 2023)
Vocabulary mastery plays an important role in learning English. The teacher's role is very important in helping students achieve their goals because acquiring a sufficient number of words is a fundamental requirement for English proficiency. This drives this study to investigate the effectiveness of the usage of crossword puzzles to enhance vocabulary mastery. This study was conducted at SMP Annur Assalafy Pasuruan. This study was conducted in a design of experiments, a semi-empirical study using quantitative techniques. The sample used in this study included students from class 7 of SMP Annur Assalafy Pasuruan, with a total of 36 students in the two classes. Class 7A is the control class and Class 7B is the experimental class. The instrument used in this survey is a multiple-choice question with up to 20 test items. The records series strategies used in this study have been pre-test, treatment, and post-test. The results of this study show that the use of crossword puzzles effectively improves students' vocabulary. According to the SPSS calculation results, the scores obtained in the experimental classes after treatment are higher than those obtained before treatment. Therefore, from the hypothesis test, the value of Sig is 0.00, which is <0.00. 0.05, so H0 is not accepted and Ha is accepted. This means that media crosswords puzzle influence English vocabulary (Y). As a result, crossword puzzle affect the increase in English vocabulary proficiency among 7th-grade students of SMP Annur Assalafy Pasuruan.